Calcium deposition within coronary atherosclerotic lesion: Implications for plaque stability. (August 2020) - Jinnouchi, Hiroyuki; Sato, Yu; Sakamoto, Atsushi; Cornelissen, Anne; Mori, Masayuki; Kawakami, Rika; Gadhoke, Neel V.; Kolodgie, Frank D.; Virmani, Renu; Finn, Aloke V.
Abstract: Atherosclerotic lesion progression is associated with intimal calcification. The earliest lesion that shows calcification is pathologic intimal thickening in which calcifications appear as microcalcifications that vary in size from <0.5 to 15 μm. The calcifications become larger as plaques progress, becoming punctate (>15 μm to 1 mm in diameter), fragmented (>1 mm), and eventually sheet-like calcification (>3 mm). When stratified by plaque type, maximum calcifications are observed in fibrocalcific plaques, followed by healed plaque ruptures. Lesions of acute thrombi, i.e., plaque rupture and erosions, which are the most frequent causes of acute coronary syndromes, show much less calcification than stable fibrocalcific plaques. Conversely, a calcified nodule, the least common lesion of acute thrombosis, occurs in highly calcified lesions. Pro-inflammatory cytokines observed in unstable plaques may provoke an early phase of osteogenic differentiation of smooth muscle cells (SMCs), a release of calcifying extracellular matrix vesicles, and/or induce apoptosis of macrophages and SMCs, which also calcify. Recent pathologic and imaging based studies indicate that lesions with dense calcifications are more likely to be stable plaques (fibrocalcific plaques), while micro, punctate, or fragmented calcifications are associated with either early stage plaques or unstable lesions (plaque rupture or erosion). Clinical non-invasive computed tomography (CT) studies show that the greater the calcium score, the higher the likelihood of patients developing future acute coronary events. This appears contradictory with the findings from pathologic autopsy studies. However, CT analysis of calcium subtypes is limited by resolution and blooming artifacts. Thus, areas of heavy calcification may not be the cause of future events as pathologic studies suggest. Rather, calcium may be an overall marker for the extent of disease. These types of discrepancies can perhaps be resolved by invasive or non-invasive high resolution imaging studies carried out at intervals in patients who present with acute coronary syndromes versus stable angina patients. Coronary calcium burden is greater in stable plaques than unstable plaques and there is a negative correlation between necrotic core area and area of calcification. Recent clinical studies have demonstrated that statins can reduce plaque burden by demonstrating a reduction in percent and total atheroma volume. However, calcification volume increases. In summary, pathologic studies show that sheet calcification is highly prevalent in stable plaques, while microcalcifications, punctate, and fragmented calcifications are more frequent in unstable lesions. Both pathologic and detailed analysis of imaging studies in living patients can resolve some of the controversies in our understanding of coronary calcification. Highlights: Calcification appears as microcalcifications and calcifications become larger as plaques progress. Pathologic studies show sheet calcification is highly prevalent in stable plaques. Microcalcifications, punctate and fragmented calcified areas are more frequent in unstable lesions. Fibrocalcific plaque has the highest proportion of histological calcification, followed by healed plaque rupture.